2018
DOI: 10.1093/geront/gny018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Measuring the Wellbeing of Carers of People With Dementia

Abstract: Without clear consensus, health professionals must be careful when using the term "wellbeing". To help inform healthcare policy and practice, we offer a starting point for a richer concept of wellbeing in the context of dementia that is multi-faceted to include positive dimensions of caregiving in addition to recognized aspects of burden. Standardized and robust measurements are needed to enhance research and there may be benefit from developing a more mixed, blended approach to measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…This inclusive conceptualisation of well-being is in line with the large variety of definitions (both conceptual and operational) in the literature, and with authors who have theorised that decreased well-being occurs when individuals are facing challenges that require additional adaptation and resources to meet 38. A recent systematic review of reviews illustrated that within the literature on caregivers of persons with dementia, well-being is most frequently operationalised as burden, depression, stress, quality of life, physical and mental health and the caregiver–recipient relationship 16. Based on their review, the authors suggested that quality of life can be considered one part of well-being, along with intrinsic feelings and emotions (positive mental attributes such as self-efficacy, negative mental attributes such as depression, subjective perceptions of one’s own health or well-being) and what they called ‘extrinsic factors’ (interactions with others, mental or physical health).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This inclusive conceptualisation of well-being is in line with the large variety of definitions (both conceptual and operational) in the literature, and with authors who have theorised that decreased well-being occurs when individuals are facing challenges that require additional adaptation and resources to meet 38. A recent systematic review of reviews illustrated that within the literature on caregivers of persons with dementia, well-being is most frequently operationalised as burden, depression, stress, quality of life, physical and mental health and the caregiver–recipient relationship 16. Based on their review, the authors suggested that quality of life can be considered one part of well-being, along with intrinsic feelings and emotions (positive mental attributes such as self-efficacy, negative mental attributes such as depression, subjective perceptions of one’s own health or well-being) and what they called ‘extrinsic factors’ (interactions with others, mental or physical health).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Although there are also gratifying and positive aspects of caregiving for many caregivers of persons with dementia,15 they are often considered a vulnerable population due to the intensity of caring demands, risk of burden and other negative consequences. This perspective is reflected in the literature on caregiver well-being, which primarily focuses on deficits and how to ameliorate negative caregiver outcomes 16…”
Section: Introductionmentioning
confidence: 99%
“…Well-being in the context of dementia has been operationalized in various ways with no clear consensus on the definition (Cunningham et al, 2018, Tyack and Camic, 2017, Kaufmann and Engel, 2014). Several measures have been developed to capture an individual’s subjective experience of well-being in the general population, but in the dementia context researchers more often use measures of depressive symptoms and quality of life (QOL) separately or in combination with other measures to represent at least the physical and mental health aspects of well-being (Dawson et al, 2013, Stites et al, 2017).…”
Section: Defining Well-beingmentioning
confidence: 99%
“…In addition to depressive symptoms and quality of life, some researchers characterize care-related strain (i.e. caregiver burden, or the subjective strain experienced as a result of providing care) as a defining component of CPs’ well-being (Arthur et al, 2017, Cunningham et al, 2018). However, according to the Stress Process Model (SPM: the model used to guide this study), care-related strain, labeled “role overload” in the SPM, is defined as a primary stressor that is predictive of well-being (Pearlin et al, 1990, Judge et al, 2010).…”
Section: Stressors and Strainsmentioning
confidence: 99%
See 1 more Smart Citation